ANALISIS PENGARUH TINGKAT ADOPSI TEKNOLOGI PERTANIAN TERHADAP PENINGKATAN PRODUKTIVITAS PADI DI NIAS SELATAN - Zega, Ujianhati (BUANA SAINS, 2025)
Enhancing rice productivity is vital for food security in developing regions. This study analyzes the adoption of high-yield varieties (HYVs) and agricultural machinery among rice farmers in South Nias and evaluates their impact on yields. Employing a mixed-methods approach, data were collected via a survey of 214 purposively sampled farmers, supplemented with in-depth interviews. The results indicate low adoption rates: only 25% of farmers use HYVs, and approximately 20% use machinery. Key barriers identified include limited access, high costs, and insufficient technical information and training. Despite these challenges, statistical analysis confirms that the adoption of both technologies has a significant positive effect on rice productivity. Farmers using these technologies achieved markedly higher yields compared to non-adopters. The study concludes that the potential of agricultural technology remains underutilized in South Nias due to critical access and knowledge gaps.Â